An international, stepped wedge, cluster-randomized trial investigating the 0/1-h algorithm in suspected acute coronary syndrome in Asia: the rational of the DROP-Asian ACS study - Inoue, Kenji; Chieh, Jack Tan Wei; Yeh, Lim Chiw; Chiang, Shuo-Ju; Phrommintikul, Arintaya; Suwanasom, Pannipa; Kasim, Sazzli; Ahmad, Bakhtiar; Idrose, Alzamani Mohammad; Salleh, Farina Mohd; Oyamada, Shunsuke; Hirano, Yohei; et al. (Trials, 2022)
Background: More than half of the world’s population lives in Asia. With current life expectancies in Asian countries, the burden of cardiovascular disease is increasing exponentially. Overcrowding in the emergency departments (ED) has become a public health problem. Since 2015, the European Society of Cardiology recommends the use of a 0/1-h algorithm based on high-sensitivity cardiac troponin (hs-cTn) for rapid triage of patients with suspected non-ST elevation acute coronary syndrome (NSTE-ACS). However, these algorithms are currently not recommended by Asian guidelines due to the lack of suitable data. Methods: The DROP-Asian ACS is a prospective, stepped wedge, cluster-randomized trial enrolling 4260 participants presenting with chest pain to the ED of 12 acute care hospitals in five Asian countries (UMIN; 000042461). Consecutive patients presenting with suspected acute coronary syndrome between July 2022 and Apr 2024 were included. Initially, all clusters will apply “usual care” according to local standard operating procedures including hs-cTnT but not the 0/1-h algorithm. The primary outcome is the incidence of major adverse cardiac events (MACE), the composite of all-cause death, myocardial infarction, unstable angina, or unplanned revascularization within 30 days. The difference in MACE (with one-sided 95% CI) was estimated to evaluate non-inferiority. The non-inferiority margin was prespecified at 1.5%. Secondary efficacy outcomes include costs for healthcare resources and duration of stay in ED. Conclusions: This study provides important evidence concerning the safety and efficacy of the 0/1-h algorithm in Asian countries and may help to reduce congestion of the ED as well as medical costs.
Gesehen am 23.01.2023